(untitled) - MacKinnon, Barbara (Belmont, Calif., 1995)
Contents: Ethics and ethical reasoning; Ethical relativism; Egoism; Utilitarianism; Kant's moral theory; Natural law and natural rights; Virtue ethics...
Keywords: Ethics,Đạo đức học